The Perceived Views of Principals and Supervisors towards Their Ethical Leadership in Some Selected Primary Schools of Eastern Ethiopia - Birhanu Sintayehu Alemu; Bahar Adem Abdillahi (Bina Nusantara University, 2020)
The research’s objectives were to assess the extent to which principals and supervisors practice ethical code of conduct in leading teachers in primary schools, identify differences among leaders related to their personal characteristics, and identify immoral practices leaders experience in the schools. The research participants were 120 principals, 63 supervisors, and 62 teachers selected using stratified and available sampling techniques. The quantitative data obtained through questionnaire were analyzed by descriptive and inferential statistics. The findings of the research reveal that school leaders are moderately ethical in their schools’ administration. There is no significant difference in the dimensions of ethical leadership practice with reference to positions and fields of study school leaders possess. However, there is a significant difference in experience in a leadership position and academic qualification as well as between males and females. Teachers perceive that school leaders use mainly deception, abuse, harassment of subordinates, diminished dignity of employees, and breach of the agreement. It is suggested that school leaders should have professional scaffolding and training in fostering ethical leadership behavior to lead schools successfully. Those interested may conduct more detailed research considering secondary schools.